Human interface and the management of information. applications and services : 18th International Conference, HCI International 2016, Toronto, Canada, July 17-22, 2016. Proceedings /: applications and services : 18th International Conference, HCI International 2016, Toronto, Canada, July 17-22, 2016. Proceedings. Part II : (2016) - Unknown
No abstract available